RECENT DYNAMICAL FEATURES OF TYNDALL AND GREY GLACIERS, FROM SOUTHERN PATAGONIAN ICEFIELD, BY USING SATELLITE REMOTE SENSING TECHNIQUES - Luzardi, A. C. M.; Cardenas Mansilla, Carlos Alberto (My University, 2020)
Most glaciers in Patagonia have been rapidly shrinking during the past decades in response to ongoing global warming. To extend techniques to monitor their dynamics is crucial to understand individual glacier response to climate change and its consequences. In that context, our study aims to investigate recent dynamic behaviour of two near-site outlet glaciers placed at the Southern Patagonian Icefield (Tyndall and Grey glaciers) with the usage of simple and cheap remote sensing techniques. Sentinel-1 images were used to estimate surface velocity by using the Offset-tracking algorithm, while Sentinel-2 images were used to estimate area change in the ice front. Moreover, climatic variables (e.g., accumulated precipitation and air temperature) were analysed in order to assess its influence on glacier dynamics. Our results indicates that precipitation rather then temperature changes has been playing a major role in both glaciers retreat. While Tyndall tends to stabilize its retreat, Grey exponentially enhances retreat by its east tongue. Additionally, mean ice speed was of 0.448 +/- 0.242 m.day(-1) for Grey and 0.439 +/- 0.245 m.day(-1) for Tyndall, which agrees with literature. However, high ice speeds near the ice front indicated by previous work could not be captured here. Our results also suggests that ice flow is a delayed response of precipitation in the accumulation zone, and that may be the cause of decrease in Tyndall's retreat. Overall, Offset-tracking is an useful tool for studying time series of Patagonian glaciers dynamics. It should be used carefully, however, around high dynamical regions such as the glacier terminus.
Keywords: glaciology; ice dynamics; offset-tracking; sentinel; ice velocity